2020
DOI: 10.1016/j.arth.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Current Preclinical Testing of New Hip Arthroplasty Technologies Does Not Reflect Real-World Loadings: Capturing Patient-Specific and Activity-Related Variation in Hip Contact Forces

Abstract: Keywords:total hip arthroplasty hip contact force functional outcomes activities of daily living biomechanics a b s t r a c t Background: Total hip arthroplasty (THA) implants are routinely tested for their tribological performance through regulatory preclinical wear testing (eg, ISO-14242). The standardized loading conditions defined in these tests consist of simplified waveforms, which do not specifically represent in vivo loads in different groups of patients. The aim of this study is to investigate, throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Moreover, the recruited participants were all rather young, fit, and active and therefore do not represent the general population. Subject demographics, such as age, BMI, and sex, have been previously shown to relate to HCFs ( De Pieri et al, 2019 ; Lunn et al, 2020 ). We did not find any statistically significant correlation between femoral torsion values and age or BMI in our investigated cohort, nor did we find a statistically significant difference between torsional values of males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the recruited participants were all rather young, fit, and active and therefore do not represent the general population. Subject demographics, such as age, BMI, and sex, have been previously shown to relate to HCFs ( De Pieri et al, 2019 ; Lunn et al, 2020 ). We did not find any statistically significant correlation between femoral torsion values and age or BMI in our investigated cohort, nor did we find a statistically significant difference between torsional values of males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative evaluation of the muscle lever arms suggested that the effect of these torsional deformities might be more pronounced for pathological ranges of femoral torsion, when the moment-generating capacity of the abductor muscles is substantially reduced. This study was also limited to an analysis of gait, which represents the most commonly performed daily activity ( Morlock et al, 2001 ); however, musculoskeletal modeling can be used to accurately assess HCFs during various activities of daily living ( De Pieri et al, 2019 ; Lunn et al, 2020 ), in which patients with hip pathologies could present more physical impairments ( Diamond et al, 2015 ; Kierkegaard et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should therefore aim to include various combinations of anatomical morphologies and implant placements, possibly based on clinical observations, and investigate them in a larger representative population and during different daily activities. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the regulatory preclinical testing standard ISO 14242-1 prescribes a simplified gait cycle, with a vertical load and sinusoidal waveforms for the rotation angles. As discussed in Lunn et al 1 and Fabry et al, 2 current preclinical tests of HAs are able to capture neither the variation in loads and kinematics of daily activities, nor the one among patients, although this is becoming more and more important: indeed, hip arthroplasty is performed in increasingly younger patients, 3 whose implants can be subjected to high loads, for example during sporting activities. Though the literature counts many studies on experimental wear tests, most of them are based on simplified walking conditions and only rarely different motor tasks, such as jogging, are considered.…”
Section: Introductionmentioning
confidence: 99%
“…4,18 Regarding the first issue, musculoskeletal (MSK) modelling represents a valuable option to estimate joint loads starting from non-invasive motion analysis. 1,[19][20][21] This approach is adopted in the present study with the aim to define a general procedure for wear prediction of MoP HAs, which could be used in in silico pre-clinical trials, investigating the effect of several daily living activities on wear. Motion analysis data collected for a subject with a right HA during walking, fast walking, lunge, squat and stair negotiation from the dataset provided by Lunn et al 1,22 and LLJ 23 are given as input to an MSK model developed in OpenSim to estimate both joint angles and joint reaction forces.…”
Section: Introductionmentioning
confidence: 99%